Factors affecting the introduction and distribution of fungi in Vestfold Hills, Antarctica - Downs, Jamie (2004)
The impact of human disturbance on fungal flora around Davis Station and the Vestfold Hills in Antarctica (68 0 35'S 77" 58'E) was examined by monitoring air spora and soil fungi over a 12 month period in 2001.